The effect of dietary carbohydrate quality on depression and anxiety levels in adolescents - Ülger, Taha Gökmen; Sürücü, Bensu; Menekşe, Ayşe Ebrar; Çakmak, Yağmur; Fidan, Şura; İncekara, Berre (Frontiers in Nutrition, 2025)
BackgroundGiven that the quality of carbohydrate intake, rather than quantity alone, may influence psychological health, particularly during adolescence, this study aimed to evaluate the relationship between dietary carbohydrate quality and depression and anxiety levels in adolescents.MethodsThis cross-sectional study was conducted with a sample of 192 second-year high school students from Bolu (Turkey). Participants’ 24-h retrospective food consumption records were collected, and the data were analyzed through the Nutrition Information System to calculate the energy, macro, and micronutrient content of their diets. Dietary carbohydrate quality was evaluated using a quintile-based scoring system created according to criteria such as glycemic index, total fiber intake, the ratio of whole grains to total grains, and the ratio of solid carbohydrates to total carbohydrates, with total scores ranging from 4 to 20 points. Depression and anxiety levels were assessed using the Beck Depression Inventory and the Beck Anxiety Inventory.ResultsThe analysis results revealed a statistically significant decrease in depression and anxiety levels as dietary carbohydrate quality increased (p < 0.05). The group with the lowest carbohydrate quality had the highest levels of depression and anxiety, and these individuals were found to have higher energy/fiber and carbohydrate/fiber ratios (p < 0.001). Moreover, adolescents with a habit of skipping main meals were found to have significantly higher anxiety scores (p < 0.05). Sodium, phosphorus, and vitamin A intakes exceeded recommended levels among male adolescents, whereas both sexes demonstrated generally insufficient intake of dietary fiber and various micronutrients, including vitamins E and C, riboflavin, pyridoxine, folate, potassium, calcium, magnesium, iron, and zinc.ConclusionThe results indicate that adolescents with low carbohydrate quality and irregular meal patterns are at risk of depression and anxiety. Nutritional interventions aimed at addressing imbalances in the intake of macro and micronutrients and improving carbohydrate quality are thought to play an important role not only in preventing metabolic diseases but also in supporting psychological well-being.